Funcionamiento familiar y personalidad en estudiantes de la Institución Educativa Secundaria Andrés Avelino Cáceres, Puno 2021 - Reyes Bedoya, Lilia Jacinta (2022)
Objective: The main objective of this research is to determine the relationship between family functioning and personality in students of the Andrés Avelino Cáceres Secondary Educational Institution, Puno 2021. Methodology: It corresponds to the quantitative research approach, of an applied type, relational level, and with a non-experimental, cross-sectional design. The data collection technique used was the survey and psychometry, its instruments were the family cohesion and adaptability scale FACE III and the Eysenck personality inventory for children (JEPI), these instruments were adapted and validated for the Peruvian reality. Participants: The study sample was made up of 119 high school students, belonging to the first, second, and third grade. The projected sample was 125 students, obtained in a probabilistic way, but the executed sample was 119 students since under the elimination criterion, 6 participants had to withdraw. Results: The results obtained in the study show that 52.80% are male and 47.20% female, in the family functioning variable, 83.19% refer to being balanced and 8, 40% middle range respectively. Regarding personality, 66.39% refer that Introversion-Extroversion is medium level, while neuroticism-stability is medium in 51.26%. Conclusions: The conclusions of the study refer that there is a relationship between family functioning and personality in students of the Andrés Avelino Cáceres Secondary Educational Institution, Puno 2021 (r = 0.340; p = 0.000). Keywords: Family functioning, personality, cohesion, adaptability, adolescents.